The Predictability of Family Structure for Coping ‎Strategies with Psychological Stress among College ‎Students - Smadi, Ahma; Alquraan, Mayadah (Jordan Journal of Educational Sciences, 2020)
This study aimed at identifing the predictability of family structure for psychological stress coping strategies among college students. A volunteer convenient sample of (726) undergraduate college students at a Jordanian University, answered the Coping Strategies Scale which was used to achieve the aim of the study after considering its pychometric properties. The results indicated that the strategy of solving problems and interactive coping strategy were ranked first, whereas the relaxing and entertainment strategy was the last. Furthermore, the results indicated that multiple regression analysis suggests differences in the coping strategies among students based on the variables of (birth- order in favor of the last child in self blaming strategy, family monthly income in favor of less than 500 JD or less and fathers with master degrees or higher in the leisure and relaxation strategy, and level of father education in favor of high Diploma or less in feelings and religion strategies).